Prosedur Pelaksanaan Pengisian Dan Pengolahan Data Sensus Harian Rawat Inap Hingga Menjadi Sumber Data Di RSUD dr. R.M. Djoelham Binjai - Yudica Rosalina; Gatot Santosa (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Health service facilities according to the Regulation of the Minister of Health of the Republic of Indonesia Number 269 / MENKES / PER / II1 / 2008 are places for organizing health service efforts that can be used for medical or dental practice. Hospitals are one example of health service facilities. Descriptive research is research that is intended to investigate conditions, conditions or things that have been mentioned, the results of which are presented in the form of research reports. The research design used in this study is a cohort survey study. The location of the research will be carried out at Dr. R.M DJOELHAM BINJAI Regional Hospital located on Jl. Sultan Hasanuddin No. 9, This research began in June - July 2019. Population is a group of subjects who are the objects or targets of research, who have certain characteristics and are determined by researchers to be able to draw conclusions. Based on the definition above, the population of this study is the inpatient nurses who carry out the implementation of the daily inpatient census filling and the process of processing the daily inpatient census in medical records. The sample in this study is the population or total population recorded in the implementation of filling and processing the daily inpatient census data. The subjects used in this study were 1 medical records officer and 7 nurses. The data collection technique that will be used in this study using qualitative research, the primary data source is interviewing medical records officers and inpatient nurses and the secondary data source in this study is the daily inpatient census form from each inpatient room. The data collection technique also uses more interview lists, observations and documentation studies